Genetic factors for susceptibility to and manifestations of neuromyelitis optica - Matsushita, Takuya (Ann Clin Transl Neurol, 2020)
OBJECTIVE: To identify genetic factors associated with susceptibility to and clinical features of neuromyelitis optica spectrum disorders (NMOSD). METHODS: Genome‐wide single nucleotide polymorphism (SNP) genotyping was conducted in 211 Japanese patients with NMOSD fulfilling the 2006 criteria with or without anti‐aquaporin‐4 (AQP4) antibody and 1,919 Japanese healthy controls (HCs). HLA‐DRB1 and HLA‐DPB1 alleles were genotyped in 184 NMOSD cases and 317 HCs. Multiple sclerosis (MS) risk alleles outside the major histocompatibility complex (MHC) region were tested in NMOSD and MS genetic burden (MSGB) scores were compared between HCs and NMOSD. RESULTS: A SNP (rs1964995) in the MHC region was associated with NMOSD susceptibility (odds ratio (OR) = 2.33, P = 4.07 × 10(−11)). HLA‐DRB1*08:02 (OR = 2.86, P = 3.03 × 10(−4)) and HLA‐DRB1*16:02 (OR = 8.39, P = 1.92 × 10(−3)) were risk alleles for NMOSD susceptibility whereas HLA‐DRB1*09:01 was protective (OR = 0.27, P = 1.06 × 10(−5)). Three MS risk variants were associated with susceptibility and MSGB scores were significantly higher in NMOSD than in HCs (P = 0.0095). A SNP in the KCNMA1 (potassium calcium‐activated channel subfamily M alpha 1) gene was associated with disability score with genome‐wide significance (rs1516512, P = 2.33 × 10(−8)) and transverse myelitis (OR = 1.77, P = 0.011). KCNMA1 was immunohistochemically detected in the perivascular endfeet of astrocytes and its immunoreactivity was markedly diminished in active spinal cord lesions in NMOSD. INTERPRETATION: Specific HLA‐DRB1 alleles confer NMOSD susceptibility and KCNMA1 is associated with disability and transverse myelitis in NMOSD.